TINGKAT PENGETAHUAN DAN SIKAP PEGAWAI BANK NEGARA INDONESIA KANTOR LAYANAN NASABAH JALAN AHMAD YANI KOTA PADANG MENGENAI COVID-19 - Salsabila, Vasya Maharani; Bahar, Elizabeth; Suchitra, Avit (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
The Covid-19 pandemic, which discovered in the city of Wuhan, China, infects through respiratory droplets that are released when an infected person coughs, sneezes, or talks. The importance of education, isolation, preventative measures, prevention of transmission control, and treatment are important steps to control Covid-19 according to the World Health Organization (WHO). The government's efforts to control Covid-19 is by issuing guidelines over Covid-19 and health protocol regulations in workplaces that have a high risk of Covid-19 transmission, such as banking. The importance of implementing health protocols in the form of knowledge and attitudes from banking employees regarding Covid-19 can reduce the level of Covid-19 cases and prevent new cases. This research is a descriptive observational study with a total sampling technique of 76 permanent employees of Bank Negara Indonesia Ahmad Yani Service Office using primary data obtained using a questionnaire which is then analyzed using a computerized system. The results showed that respondents with a good and sufficient level of knowledge about Covid-19 had the same percentage (46.1%) and the majority of employees (43.4%) had a good attitude towards Covid-19. The conclusion of this study is that the majority of respondents have a good percentage of knowledge and attitude in dealing with Covid-19